2014
DOI: 10.2319/070714-476.1
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between objective and subjective evaluation of profile in bimaxillary protrusion patients after orthodontic treatment

Abstract: Cephalometric measurements of lip position, incisor position, and chin morphology were key parameters correlated to facial esthetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 19 publications
3
22
0
Order By: Relevance
“… 14 , 15 , 26 Among the measurements of lip position, the distances from the upper and lower lips to the E line, Z angle, and H angle have been regarded as suitable assessments in different study samples. 21 , 22 , 26 28 In addition, chin prominence and variables related to the contour of the mentolabial fold are sensitive parameters in the facial evaluation. 21 , 22 Consistent with previous studies, our results demonstrated that the distances from the upper and lower lips to the E line, the H angle, the distance from the lower lip to the H line (all of which represent the lip position), and the PMA (which represents the chin morphology) had a negative influence on the entire facial attractiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 14 , 15 , 26 Among the measurements of lip position, the distances from the upper and lower lips to the E line, Z angle, and H angle have been regarded as suitable assessments in different study samples. 21 , 22 , 26 28 In addition, chin prominence and variables related to the contour of the mentolabial fold are sensitive parameters in the facial evaluation. 21 , 22 Consistent with previous studies, our results demonstrated that the distances from the upper and lower lips to the E line, the H angle, the distance from the lower lip to the H line (all of which represent the lip position), and the PMA (which represents the chin morphology) had a negative influence on the entire facial attractiveness.…”
Section: Discussionmentioning
confidence: 99%
“… 18 20 Some researchers have explored the relationship between cephalometric measurements of the lip position and facial esthetics; however, the results are far from conclusive. 21 24 Additionally, few studies have investigated the contributions of different facial parts to the entire facial esthetics. The potential correlation between objective measurements and subjective evaluations of different facial parts requires further examination.…”
Section: Introductionmentioning
confidence: 99%
“…But the teeth especially the anterior teeth are forwardly placed leading to an appearance of prominence of soft tissues (lip). 1,2 In this case the molar canine and incisor relation are class I. Furthermore, in bimaxillary prognathism, the jaw bones (basal) remain forward in relation to to the cranial bone.…”
Section: Bimaxillary Protrusionmentioning
confidence: 97%
“…The negative perception related to the lips protrusion leads many patients to seek orthodontic A Preferência Estética do Perfil de Indivíduos com Má-Oclusão de Classe II Tratados com e sem Extração treatment. Based on that, the same level of importance has to be given to both, establishment of a functional occlusion and the improvement of the facial profile 4 .…”
Section: The Esthetic Profile Preferences Of Class II Malocclusion Pamentioning
confidence: 99%